Time-dependent Seismic Footprint of Thermal Loading for Geothermal Activities in Fractured Carbonate Reservoirs - Wassing, B. B. T.; Candela, T.; Osinga, S.; Peters, E.; Buijze, L.; Fokker, P. A.; Van Wees, J. D. (Frontiers in Earth Science, 2021)
This paper describes and deploys a workflow to assess the evolution of seismicity associated to injection of cold fluids close to a fault. We employ a coupled numerical thermo-hydro-mechanical simulator to simulate the evolution of pressures, temperatures and stress on the fault. Adopting rate-and-state seismicity theory we assess induced seismicity rates from stressing rates at the fault. Seismicity rates are then used to derive the time-dependent frequency-magnitude distribution of seismic events. We model the seismic response of a fault in a highly fractured and a sparsely fractured carbonate reservoir. Injection of fluids into the reservoir causes cooling of the reservoir, thermal compaction and thermal stresses. The evolution of seismicity during injection is non-stationary: we observe an ongoing increase of the fault area that is critically stressed as the cooling front propagates from the injection well into the reservoir. During later stages, models show the development of an aseismic area surrounded by an expanding ring of high seismicity rates at the edge of the cooling zone. This ring can be related to the “passage” of the cooling front. We show the seismic response of the fault, in terms of the timing of elevated seismicity and seismic moment release, depends on the fracture density, as it affects the temperature decrease in the rock volume and thermo-elastic stress change on the fault. The dense fracture network results in a steeper thermal front which promotes stress arching, and leads to locally and temporarily high Coulomb stressing and seismicity rates. We derive frequency-magnitude distributions and seismic moment release for a low-stress subsurface and a tectonically active area with initially critically stressed faults. The evolution of seismicity in the low-stress environment depends on the dimensions of the fault area that is perturbed by the stress changes. The probability of larger earthquakes and the associated seismic risk are thus reduced in low-stress environments. For both stress environments, the total seismic moment release is largest for the densely spaced fracture network. Also, it occurs at an earlier stage of the injection period: the release is more gradually spread in time and space for the widely spaced fracture network.